Design Of Sales Information System In Website-Based Isaylees Sport Store - Ekhwan Juvana; Endang Lestariningsih (Institut Teknologi Bisnis AAS Indonesia, 2022)
Abstract— This study aims to create a website-based sales information system at the Isaylees Sport store. The design and manufacture of a sales information system at the Isaylees Sport store is carried out to make it easier for sellers to manage sales and purchase data. In this system, sellers are expected to be able to market products with a wider range and sell products effectively and efficiently. In addition to providing convenience for sellers, this system also makes it easy for customers to make buying and selling transactions at the Isaylees Sport store. The method used in system design is through the stages of making DFD and ERD diagrams. Results from this research, namely the sales information system at the website-based isaylees Sport store that has been designed to have automatic payment features using a payment gateway, automatic postage checks and order tracking. The system that has been designed also provides convenience for sellers and buyers. The result of this research is an e-commers application that is used in sales transactions.